Deaf professionals and designated interpreters : a new paradigm - Hauser, Peter C.; Finch, Karen L.; Hauser, Angela B. (Book collections on Project MUSE., 2008)
"The essays within this collection define a new model for interpreting that depends upon strong partnerships between the growing number of deaf professionals and their interpreters. Editors Peter C. Hauser, Karen L. Finch, and Angela B. Hauser have called upon more than a score of widely respected researchers to discuss the new dynamics of interpreting for deaf professionals." "These anecdotal chapters demonstrate the critical complexity of the relationships between professionals and interpreters, a revolutionary transformation that will be appreciated by interpreter preparation programs, instructors, interpreters, and deaf people alike."--Jacket